Digital platform ecosystems for sustainable innovation: Toward a new meta-organizational model? - Mario Calabrese; Antonio La Sala; Ryan Patrick Fuller; Antonio Laudando (Administrative Sciences, 2021)
This work aims to develop a conceptual model to support countries, institutions, and firms toward the accomplishment of present Agenda 2030 sustainability goals. The last two decades have seen a growing interest in sustainability. Climate change, resource scarcity, multipolarity of interests, mistrust and delegitimization of institutions are just some of the critical issues that need to be addressed. There is broad consensus on the urgency of generating further social, environmental, and economic innovation to address these challenges, reshaping global markets, and offering new spaces of action to firms and institutions. Accordingly, there also is a wide search for new models of organizing firms. Digital platforms are among those. Moreover, since digital platforms require coordination among multiple actors and interests in order to succeed, they may also be conceptualized as meta-organizations, less hierarchical than firms yet more tightly coupled than markets. However, despite the wide literature on platforms, this organizational lens seems not to have been taken into the right consideration. This conceptual work aims to fill this gap, providing a framework that clarifies why and how a digital platform ecosystem could configure a sustainable meta-organizational model, and also providing the main steps to build it.
Keywords: 350; digital platform ecosystem; organizational model; sustainable innovation